Analytical solutions for multiwell hydraulic barrier capture zone defining - Colombo, Loris; Cantoni, Martino; Alberti, Luca; Francani, Vincenzo (Italian journal of engineering geology and environment, 2012)
As it is well-known, the groundwater wells are often incorrectly located, reducing the hydraulic barrier effectiveness. A quick method for delineating the capture curve also for non co-linear geometry of a wells barrier is thus required. Therefore this paper deals with a non linear location of wells, as a solution of this problem developing an analytical-graphical method to design a barrier whose dimensions (particularly the capture zone width near the wells) are fair sized for the containment of pollution plumes. The suitability of graphical method is validated and supported by a comparison between analytical computed curve capture and numerical one, as solutions reached by Modflow code.